(untitled) (Applied Biological Research, 2023)
Botanical products are encouraged for mosquito control because of their low cost, rapid degradation, and low toxicity. The hexane extracts of Cinnamomum cassia (C) and Zingiber officinale (Z) were assessed alone or in combination on the 3rd instar of Culex pipiens. The LC50 values of C. cassia and Z. officinale against Cx. pipiens were 317.61 and 269.4 µg mL-1, respectively. The Z75%: C25% ratio was the most promising among the different combinationtested, with IC50 value of 251.76 µg mL-1. The histological sections of extract-treated larvae (C25%: Z75%) induced degeneration of epithelial cells, degradation of microvilli, and loss of nuclei. Antioxidant activity and phenolic content of Z. officinale hexane extract showed a linear relationship. Z. officinale extract at 60.5 µg mL-1 possessed the highest hemolytic activity (73.9 ± 0.5%). Our results revealed that the combined hexane extracts of C. cassia and Z. officinale provided promising larvicidal action against Cx. pipiens.